PROCEDURE FOR REGISTRATION OF MARRIAGE AGREEMENTS AFTER THE MARRIAGE IS DONE - Yulia Hesti (Progressive Law Review, 2022)
Marriage can sometimes give rise to problems regarding property, namely regarding joint property with husband and wife as well as personal property and or innate property. On the basis of selfishness, it is often not realized that one party feels that all the wealth obtained in marriage is the result of his own hard work. This is what often triggers a commotion so that household trips are not harmonious and in line. The problem studied is how the procedure for registering a marriage agreement after the marriage has been carried out. The method used is a normative juridical way. Procedure for Registration of Marriage Agreements After Marriage is carried out based on the Post-Constitutional Court Decision Number 69/PUU-XIII/2012 and Circular Letter of the Director General of Dukcapil Number 472. 2/5876/Dukcapil is to make a deed of agreement made before a notary, prepare the conditions that have been determined, one of which is a marriage certificate of husband and wife, then registered with the local Disdukcapil where the place to issue the marriage certificate is for non-Muslims, and KUA for Muslims. The advice given to the relevant agencies in this case Disdukcapil and KUA which handles the issue of marriage agreements in order to provide education and socialization to the community. and to KUA for Muslims. The advice given to the relevant agencies in this case Disdukcapil and KUA which handles the issue of marriage agreements in order to provide education and socialization to the community. and to KUA for Muslims. The advice given to the relevant agencies in this case Disdukcapil and KUA which handles the issue of marriage agreements in order to provide education and socialization to the community